Peningkatan Prestasi Belajar Matematika Melalui Penguatan Minat dan Disiplin Belajar - Dedy Yusuf Aditya; Ai Solihah; Siti Julaeha (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this research is to determine: (1) The combined influence of learning interest and discipline on mathematics learning achievement. (2) The influence of students' learning interest on mathematics learning achievement. (3) The influence of discipline on mathematics achievement. The method used is a survey method. The total population in this study consists of 600 students, and the sample taken for this research is 10% of the population, which is 60 students. The results of hypothesis testing indicate: (1) There is a significant combined influence of learning interest and discipline on mathematics learning achievement. This is evidenced by the significance value of 0.000 < 0.05 and an F value of 27.097. (2) There is a significant influence of learning interest on mathematics achievement. This is evidenced by the significance value of 0.000 < 0.05 and a t value of 5.544. (3) There is a significant influence of discipline on mathematics learning achievement. This is evidenced by the significance value of 0.035 < 0.05 and a t value of 2.155. This research is valuable for enhancing the quality of teaching and the mathematics learning achievement of students in a Private Vocational School in Central Jakarta.